PENGARUH BIAYA OPERASIONAL TERHADAP KINERJA KEUANGAN PADA PADA PT.PELNI (PERSERO) CABANG PAREPARE - Merlindayani, Merlindayani; Yusuf, Syarifuddin (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine the effect of operational costs on financial performance at PT. Pelni (Persero) Parepare Branch by using financial analysis techniques and simple linear regression analysis. The data collection techniques used in this study were observation, interviews, and documentation. The object of this research is the income statement and balance sheet. The data analysis carried out in this study was using quantitative methods. The results of this study using financial analysis techniques, namely ROA profitability, showed that the results of financial statements fluctuated from year to year and simple linear regression analysis techniques explained that operational costs had a significant effect on financial performance at PT.Pelni (Persero) Parepare Branch.